Hypertrophic Pachymeningitis in a Southern Chinese Population: A Retrospective Study - Xiao, Xuewen; Fu, Dongni; Feng, Li (Frontiers in Neurology, 2020)
Aims: To investigate the causes, clinical characteristics, imaging features, and therapeutic implications of hypertrophic pachymeningitis (HP) in a southern Chinese population. Methods: We retrospectively analyzed 48 patients with HP with different causes from 1 January 2006 to 31 December 2018. Clinical manifestation, laboratory findings, and neuroimaging results were evaluated in all HP patients. Results: The mean age at onset was 50 ± 12 years. The most common diagnosis was idiopathic HP (67%), followed by antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (15%), tuberculous meningitis (8%), viral meningitis (6%), and bacterial meningitis (4%). Headache was the most common symptom. The most frequently changed laboratory finding was elevated erythrocyte sedimentation rate (ESR). Imaging was characterized by cerebral or spinal dura mater enhancement in MRI scan with contrast. Enhancements were mainly located in the posterior fossa for idiopathic HP; frontal, parietal, and occipital lobes for ANCA-related HP; and posterior fossa for tuberculous-associated HP. Diffuse enhancement was found in most cases, except for tuberculous-associated HP. Glucocorticoid or immunosuppressive treatment was applied in most cases. Conclusions: The etiology of HP varied among patients, with idiopathic HP being the most common. MRI showed enhancement of the dura mater, which differed according to different etiologies. Glucocorticoid or immunosuppressive agents were the primary drugs for treatment.